Chipangano: vigilantism and community responses in Mbare District, Zimbabwe, c.2000-2013 - Munyarari, Tinashe (Rhodes University, Faculty of Humanities, Department of History, 2018)
This study examines an aspect of Zimbabwe's political history, namely the emergence and operations of Chipangano vigilante group in Mbare (2000-2013) and how the community responded to the scourges of this vigilante group. This study shows that Chipangano, which means a pact, was formed with the intention to extend ZANU-PF patronage system, canvassing support and regain control of Mbare district from the MDC. The group consolidated itself as a shadow militia group for ZANU-PF that intimidated the opposition parties and coerced the general populace to attend ZANU-PF functions. It also shows that the vigilante group seized Harare City Council's duties, such as collecting gate-takings from local and long distance public transport at Mbare Bus Terminal; controlling allocations of market stalls and collecting rents from market stalls, for personal benefits. The group also politicised the access to local state property. Chipangano's collusion with ZANU-PF and state structures licensed it to engage in criminal activities with impunity, thus this thesis seeks to understand the relationship between the vigilantes, ZANU-PF and state structures. The activities of Chipangano such as abduction, intimidation, beatings, killings and displacement of people resulted in social trauma. This thesis will also explore how this phase of violence is remembered today by the research informants.
Keywords: Vigilantism -- Zimbabwe -- Mbare; ZANU-PF (Organization : Zimbabwe); Zimbabwe -- History -- 1980-; Vigilantism -- Zimbabwe -- Mbare -- Public opinion; Collective memory -- Zimbabwe Mbare